Arts-based approach in teaching gross anatomy to sports science undergraduated student: a pilot study - Papa, Veronica; Saracco, Alberto; Vaccarezza, Mauro (EDIZIONI IDELSON-GNOCCHI, 2020)
Nowadays, there is much debate about suitable methods of delivering anatomical knowledge. And the way in which anatomy is taught is also evolving. This study examined whether or not students’ learning outcomes are influenced both by the use of arts-based approaches in conjunction with the standard anatomical education based on a traditional lecture learning format curricula. Our results showed that the use of the anatomy coloring book seems to improve the motivation of students to learn anatomy as well as the knowledge retention. Moreover, most students found that they enjoyed learning anatomy the coloring method, and therefore, the use of anatomy coloring book improves and facilitates learning compared to frontal lessons or 2D atlas use.